Pengaruh Lama Kerja Terhadap Kadar Merkuri (Hg) Dalam Urin Pekerja Tambang Emas (Studi kasus di Desa Panton Luas Kecamatan Sawang Kabupaten Aceh Selatan) - Nur Asiah; Zul Alfian; Jazanul Anwar; Yahwardiah Siregar; Datten Bangun (Jurnal Pendidikan Kimia (JPKim), 2015)
Abstract. Mercury (Hg) is a heavy metal that is a major concern in terms of health because it is toxic to humans. This study aims to determine the effect of long working on levels of mercury (Hg) in the urine of a gold miner in the village of Panton Luas Sawang District of South Aceh. The sampling technique is total sampling as many as 30 people. The results showed that the levels of mercury in the urine of the highest gold mine workers was 3.8 μg/l and the lowest was 2.0 μg/l with mean 2.82 μg/l (SD ± 0.57), the results Chi-square test showed that the length of work to give effect to the levels of mercury in the urine of miners (p = 0.046). Further research is recommended in order to see the difference in mercury levels in people who are exposed to mercury directly with a gold miner who was not involved in the amalgamation process and the local community at risk of exposure to mercury pollution from mining activities in the village and examine the population residing in other villages in the district mentioned. Keywords: length of work, levels of mercury, urin